Antimicrobial Activity of Origanum vulgare Essential Oil against Staphylococcus aureus and Escherichia coli - Sonia Tejada-Muñoz; Denny Cortez; Jesús Rascón; Segundo G. Chavez; Aline C. Caetano; Rosa J. Díaz-Manchay; Julio Sandoval-Bances; Sonia Huyhua-Gutierrez; Lizandro Gonzales; Stella M. Chenet; Rafael Tapia-Limonchi (Pharmaceuticals)
Background/Objectives: Oreganum vulgare essential oil (OEO) is safe, effective, multifunctional, and widely used. This study aimed to evaluate OEO’s chemical composition and antimicrobial activity in vitro against S. aureus and E. coli. Methods: The composition of OEO was determined by gas chromatography–mass spectrometry (GC-MS). Results: Compounds included monoterpenes with known antimicrobial activity, such as 2-menthen-1-ol (36.33%), linalyl acetate (9.26%), terpinene-4-ol (9.01%), 4-thujanol (6.33%), menthen (5.81%), sabinene (5.18%), and carvacrol methyl ether (5.14%). Conclusions: OEO had a strong antimicrobial activity with a minimum inhibitory concentration (MIC) of 1.90 mg/mL for S. aureus and 0.49 mg/mL for E. coli after 18 h incubation. The minimum bactericidal concentration (MBC) was 7.9 mg/mL against S. aureus and 0.99 mg/mL against E. coli. Thus, OEO could be used as a natural antimicrobial against S. aureus and E. coli infections.